2009
DOI: 10.3171/2008.11.jns08827
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction after subarachnoid hemorrhage caused by ruptured aneurysms of the anterior communicating artery

Abstract: Olfactory disorders after SAH caused by rupture of the ACoA are very frequent and were present in both treatment groups. Cerebral vasospasm and frontal lobe lesions are related to worse performance on an olfactory test in patients undergoing endovascular coil embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…It has been reported that 12000 – 24000 tons of vanadium per year are generated from the burning of fossil fuels (Bertine and Goldberg, 1971), and given that fossil fuel demand has risen considerably since then (Huntington, 2010), the emission rate attributable to fossil fuel burning has likely risen dramatically. Also, vanadium concentrations have been reported in cigarette smoke to range from 0.49 to 5.33 µg/g (Adachi et al, 1998), and smoking has been linked to olfactory dysfunction (Frye et al, 1990, Martin et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 12000 – 24000 tons of vanadium per year are generated from the burning of fossil fuels (Bertine and Goldberg, 1971), and given that fossil fuel demand has risen considerably since then (Huntington, 2010), the emission rate attributable to fossil fuel burning has likely risen dramatically. Also, vanadium concentrations have been reported in cigarette smoke to range from 0.49 to 5.33 µg/g (Adachi et al, 1998), and smoking has been linked to olfactory dysfunction (Frye et al, 1990, Martin et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…13 Older age has also been identified in several studies as a risk factor to olfaction after surgical clipping of a ruptured aneurysm. 9,13 Similarly, the current authors discovered a higher incidence of olfactory dysfunction after SAH in patients aged ≥ 55 years. 13 Yet, in the present study of patients with unruptured ACoA aneurysms, age did not reach statistical significance as a risk factor.…”
Section: Discussionmentioning
confidence: 81%
“…It had been thought that only serious injuries of the head with fractures of the anterior cranial fossa resulting in anatomical disruption of the olfactory filaments or tract cause permanent anosmia, but permanent anosmia can result from even trivial injuries [11]. Previous studies have reported anosmia after surgical treatment of anterior communicating artery (ACoA) aneurysms and suggest that its prevalence depends on the mode of approach to the aneurysm [6]. It has been mentioned that there are three mechanisms of olfactory nerve damage during frontal lobe retraction (depression and elevation): partial or total avulsion of the olfactory nerve from the cribriform plate [14, 6, 9]; injury during nerve dissection; and direct pressure damage [2, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported anosmia after surgical treatment of anterior communicating artery (ACoA) aneurysms and suggest that its prevalence depends on the mode of approach to the aneurysm [6]. It has been mentioned that there are three mechanisms of olfactory nerve damage during frontal lobe retraction (depression and elevation): partial or total avulsion of the olfactory nerve from the cribriform plate [14, 6, 9]; injury during nerve dissection; and direct pressure damage [2, 9]. Cardali et al [2] suggested that maintaining the anatomic integrity of the nerve is important to preserve olfactory function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation